Tourism in the virtual age: Predicting the adoption of virtual reality applications in tourism - Wibisono, Nono; Rafdinal, Wahyu; Setiawati, Lina (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Virtual Reality (VR) has grown rapidly since the COVID-19 pandemic and continues to grow even after the pandemic is over. In the tourism industry, VR applications are often used in the tourism process to promote destinations and attract tourists to visit. Starting from the quality of VR applications, tourists will intend to use VR applications if these applications have good quality. For this reason, by assessing VR quality and incorporating it into TAM, this study aims to explore the adoption of VR applications in the tourism sector. This study included 400 VR users as participants. Using the partial least square structural equational model (PLS-SEM), a number of hypotheses were assessed. The findings demonstrate that VR quality significantly influences all TAM constructs, including attitude and intention to use. Then, attitude is significantly influenced by perceived usefulness and ease of use. Finally, the intention to use is significantly influenced by attitude. These results indicate that VR quality that is useful and easy to use will determine the adoption of VR applications in tourism. This paper advances both theory and practice by explaining the importance of VR quality and TAM in the adoption of VR applications in tourism.